Finance - Cornett, Marcia Millon; Adair, Troy A. 1964- (Troy Alton); Nofsinger, John R. (McGraw-Hill LLC, 2022)
M:Finance was developed for the undergraduate corporate finance course and designed with today's student in mind. With years of teaching experience as well market development, the author team developed a text to reflect that this critical course covers so many crucial topics and that instructors need to focus on core ideas to ensure that students are getting the preparation they need for future classes—and for their lives beyond college.